2003
DOI: 10.1159/000070280
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gonadotropin Releasing Hormone Release by Neuropeptide Y at the Median Eminence during the Preovulatory Period in Ewes

Abstract: The median eminence (ME) of the hypothalamus is known to be an important brain site where hypophysiotropic release might be regulated by excitatory and inhibitory signals impinging on their neuronal terminals. Since a role for neuropeptide Y (NPY) on preovulatory luteinizing hormone (LH) release has been suggested, we hypothesized that NPY might act at the ME to control preovulatory gonadotropin-releasing hormone (GnRH) release and thus the onset of the preovulatory surge of LH. To examine this possibility, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Direct measurement of NPY secretion in the periventricular nucleus of rats using a push-pull cannula also revealed that NPY was secreted in discrete episodes [42]. In ruminants, it has been reported that NPY neurons are located in the arcuate and periventricular nuclei, and that their axons project to many brain regions including the median eminence [43,44,45,46]. While the target of NPY released in episodic fashion is also still unclear, one possibility is that NPY activates SRIH neurons to inhibit GH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Direct measurement of NPY secretion in the periventricular nucleus of rats using a push-pull cannula also revealed that NPY was secreted in discrete episodes [42]. In ruminants, it has been reported that NPY neurons are located in the arcuate and periventricular nuclei, and that their axons project to many brain regions including the median eminence [43,44,45,46]. While the target of NPY released in episodic fashion is also still unclear, one possibility is that NPY activates SRIH neurons to inhibit GH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…NPY neurons in the arcuate nucleus of the hypothalamus have been found to project to GnRH neurons (18,19), and morphological evidence indicates colocalization of NPY receptors and GnRH neurons (18). Both in vivo and in vitro studies have demonstrated that NPY stimulates GnRH secretion (20 -26), because NPY infusion into the third ventricle of ewes significantly elevated GnRH levels in the median eminence (23), and exposure of NPY to GT1-7 cells significantly increases GnRH secretion (24). Although the stimulatory effect of NPY on GnRH neurons has been well-documented, NPY can also have an inhibitory action on GnRH release, which is associated with changes in steroidal environment, stage of development, and species (27)(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…In the preoptic area of adult sheep direct connections between NPY and GnRH have been demonstrated (Tillet et al, 1989;Norgren and Lehman, 1989). In addition, during the breeding season, infusion of NPY in the median eminence induces an advance of the onset of LH surge (Advis et al, 2003) but when infused during anoestrus season NPY has no effect (Wó jcik- Gładysz et al, 2003). According to these data in adults, we cannot exclude a direct effect of NPY onto GnRH neurons during puberty; however as far as we know, such physiological effect was never demonstrated and in adult, NPY seems to play a role during the oestrus cycle only when GnRH neurons are active, not during anoestrus season when they are quiescent.…”
Section: Discussionmentioning
confidence: 99%
“…It is distributed in numerous neuronal populations, especially in the hypothalamus of several species, including sheep (Antonopoulos et al, 1989;Chaillou et al, 2002). It is involved in many neuroendocrine functions such as the control of food intake (Chaillou et al, 2002;Barker-Gibb and Clarke, 1996;Ober and Malven, 1992;Adam et al, 1997;Polkowska and Gladysz, 2001) or reproduction (Barker-Gibb et al, 1995;Malven et al, 1995;Wó jcik-Gładysz et al, 2003;Advis et al, 2003;Estrada et al, 2003). Neuropeptide Y is also involved in the regulation of GH, and it stimulates GH secretion in the adult sheep (Morrison et al, 2003;McMahon et al, 1999), whereas in rats it suppresses GH release by stimulating somatostatin discharge (Rettori et al, 1990).…”
Section: Introductionmentioning
confidence: 99%